MAXIMIZING TECHNOLOGY IN LANGUAGE TEACHING - Cecilia Titiek Mumiati (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
In this digital era. the computer has an increasingly important role in improving all aspects of life. Most people use the computer to make their task easier andfaster. Likewise. in language teaching. it has been widely used to enhance the teaching and learning process. Learners as well as teachers can take advalltage of . computers. Some of Ihe advantages are Ihe so-called Computer Enhanced Instruction. and the electronic mail. Computer Enhanced Instruction refers to language software and courseware that learners can use either independently or in-groups. Internet as one of the most amazing inventions in the 20"' century. without a doubt. provides many advantages for teachers and learners. II is the easiest way to access different kinds of information Ihal they need for the teaching and learning process. Next. learners and teachers can make use of emails to communicate and improve their language skills. Considering the advantages of computers in language leaching both learners and teachers are encouraged to use it to improve their skills and to obtain more information.